Frequency of Cervical Nodal Metastasis in Early- Stage Squamous Cell Carcinoma of the Tongue - Ahmed,Sadaf Qadeer (2018)
Abstract Introduction Oral cavity carcinoma is an aggressive tumor, with the tongue being one of the most common subsites of involvement. Surgery is a gold standardmethod of dealing with advanced-stage tumors. However, for early-stage carcinomas of the tongue, the management remains controversial. Several studies have indicated that early-stage cancers have a high chance of occult cervical node metastasis, which, if left untreated, can greatly affect the prognosis. Certain parameters can help identify patients with occult cervical node metastases, and can avoid unnecessary neck dissection in node negative patients. Tumor thickness is one such objective parameter. Objective To estimate the frequency of cervical lymph node metastasis in patients with early-stage, node-negative (N0) squamous cell carcinoma of the tongue. Methods In-patient hospital data was reviewed from January 2013 until March 2014, and 78 patients who underwent primary resection of the tumor and neck dissection for biopsy-proven, early stage squamous cell carcinoma of the tongue were included. Data such as tumor thickness, tumor differentiation and presence of occult nodal metastasis in the surgical specimen were gathered from the histopathology reports. The frequency of subclinical cervical lymph node metastasis in patients with early-stage squamous cell carcinoma of the tongue was estimated. Results A total of 69% of the patients with tumor thicknesses > 5 mm had tumor metastases in the neck nodes, while 100% of the patients with tumor thicknesses < 5 mm had no neck nodal metastasis. Conclusion A tumor thickness > 5 mm is significantly associated with subclinical metastasis, and prophylactic neck dissection is warranted in such cases.